Effects of semaglutide on metabolism and gut microbiota in high-fat diet-induced obese mice - Sun, Luyan; Shang, Bingqing; Lv, Suyuan; Liu, Guolong; Wu, Qiu; Geng, Yue (Frontiers in Pharmacology, 2025)
BackgroundThe purpose of this study was to explore how semaglutide, a GLP-1RA, regulates serum metabolism and gut microbiota to improve obesity in mice and whether fecal microbiota transplantation (FMT) can transmit the beneficial effects of semaglutide to recipient mice.MethodsMale C57BL/6J mice were given standard diet (ND), high-fat diet (HFD), or high-fat diet with semaglutide (SHF, 100 μg/kg). Fecal microbiota transplantation was used to transplant the fecal suspension supernatant (MT) and bacteria (FMT) from SHF group mice to antibiotic-induced pseudo-germ-free mice.ResultsResults showed that semaglutide significantly reduced the body weight, body fat, FBG, and insulin levels induced by high-fat diet, and improved insulin resistance and sensitivity damage (p < 0.05). This was achieved by regulating the expression of genes related to lipid metabolism such as Pparα, Pparγ, Cpt1a, and Pgc1α in the liver and adipose tissue, as well as the appetite-related genes Leptin, Agrp, Npy, and Pomc in the hypothalamus. After stopping semaglutide intervention 4 weeks, the body weight of the mice rebounded significantly. Fecal microbiota transplantation could transmit the beneficial effects of semaglutide to recipient mice. Semaglutide and fecal microbiota transplantation affected metabolic pathways such as serum amino acid metabolism and pyrimidine metabolism in obese mice, and reshaped the composition and proportion of fecal gut microbiota in obese mice.ConclusionIn summary, semaglutide could inhibit food intake and improve obesity, regulate serum metabolism and the composition of gut microbiota in mice. Bacterial transplantation is key to transmitting the improvement brought about by fecal microbiota transplantation of semaglutide to recipient mice.